Working Capital Management and Corporate Profitability: Empirical Evidences from Nepalese Manufacturing Sector - Adhikari, Pitri Raj (Management Dynamics, 2020)
This research paper attempts to fill the gap regarding the working capital management of manufacturing firms in context of Nepal by providing empirical evidence, and moreover, this study act as foundation for future research activity because there are very few working capital management research literatures in Nepalese context. The secondary data for data analysis are retrieved from annual reports of five manufacturing firms for eight-year period from 2010/11 to 2017/18. This study examines the impact of different working capital components, i.e. inventory conversion period, receivable conversion period, payable deferred period, cash conversion cycle, debt ratio and current ratio, with profitability of a manufacturing firm, where profitability is represented by return on equity, return on assets and net income. Statistical tools used for data analysis are Pearson’s correlation, ordinary least square regression and binary logistic regression. Such that, this study found that, inventory conversion period, payable deferral period and cash conversion cycle are inversely related with the profitability of manufacturing firms, whereas, receivable conversion period , debt ratio and current ratio are positively related.